How do emergency ambulance paramedics view the care they provide to people who self harm?: Ways and means. (January 2017) - Rees, N.; Rapport, F.; Snooks, H.; John, A.; Patel, C.
Abstract: The UK has one of the highest rates of self harm (SH) in Europe, and almost four times more people die by suicide than in road traffic collisions. Emergency ambulance paramedics are often the first health professionals involved in the care of people who have self-harmed, yet little is known about the care provided or issues raised in these encounters. The aim of this study is to explore paramedics' perceptions and experiences of caring for people who SH, to inform education and policy. Semi structured interviews were conducted with paramedics, and themes generated by constant comparison coding. This paper reports two emerging themes: Firstly, professional, legal, clinical and ethical tensions, linked to limited decision support, referral options and education. The second theme of relationships with police, revealed practices and surreptitious strategies related to care and detention, aimed at overcoming complexities of care. In the absence of tailored education, guidance or support for self-harm care, ' ways and means ' have evolved which may negatively influence care and challenge ethical and legal frameworks. There is an urgent need to include evidence from this study in revised guidance and educational materials for paramedics working with people who self-harm in the prehospital emergency setting.